Targeting Lopinavir to the Mesenteric Lymphatic System by Lipophilic Ester Prodrug Approach for Improved Treatment of HIV/AIDS - Qin, Chaolong (2021)
Human immunodeficiency virus (HIV) is a lifelong disease that can destroy human immune system, thereby leading to life-threatening acquired immune deficiency syndrome (AIDS). Combined antiretroviral therapy (cART) can efficiently suppress HIV replication, but the cessation of cART usually results in viral rebound, mostly due to the presence of viral reservoirs. The mesenteric lymphatic system, including mesenteric lymph nodes (MLNs), is an important viral reservoir. In this work, lopinavir (LPV), a protease inhibitor, was selected as a drug candidate for mesenteric lymphatic targeting. In this work we focused on two main aims as follows: (1) development and validation of a sensitive HPLC-UV bioanalytical method for determination of LPV for pharmacokinetics and biodistribution studies in rats; (2) discovery of a novel lipophilic ester prodrug approach, combined with oral lipid-based drug delivery, to efficiently deliver lopinavir (LPV) to the mesenteric lymph and MLNs.